Enteral nutrition with medium-chain triglyceride compared to total parenteral nutrition in patient with chylothorax: an evidence based case report - Chintya Tedjaatmadja; Yohannessa Wulandari (World Nutrition Journal, 2024)
Introduction: Chylothorax is associated with longer length of stay, higher morbidity, mortality, and hospitalization cost. The main principle of chylothorax therapy is to reduce the chylous flow. The current nutritional management of patients with chylothorax are a low fat diet with long chain triglyceride (LCT) restriction, enteral nutrition with high medium chain triglyceride (MCT), and total parenteral nutrition. However, low fat diet with LCT restriction takes quite a long time (around 3 weeks) and requires close monitoring due to risk for malnutrition, essential fatty acid, and micronutrient deficiencies. The nutritional management determines the success of conservative therapy in chylothorax patients. The aim of this study was to determine whether a high MCT enteral diet is more superior than total parenteral nutrition regarding the resolution of chylothorax. Method: Literature searching was conducted using advanced searching in three large databases: Pubmed, Science Direct, and ProQuest using eligibility criteria determined by the authors. Quality of evidences were assessed based on GRADE Guidelines. Level evidence was determined based on Oxford Center of Evidence-based Medicine (CEBM). Result: Three systematic reviews and one cohort met the PICO and eligibility criteria that had been set. Two studies concluded that enteral nutrition was better than parenteral nutrition. One study concluded that parenteral nutrition could be considered first and one study could not conclude which kind of nutrition was better. Conclusion: Administration of high MCT enteral nutrition can be the first line therapy in patients with chylothorax and still need close monitoring during the administration. One of the factors that need to be monitored is the daily production of chylothorax volume. The results shown by these studies are inconsistent and warrant further research of high-quality studies regarding the treatment of chylothorax.